STEYN, Colin Fraser Inventory of documents - STEYN, Colin Fraser (ARCA, 2018)
Private papers of C.F. Steyn, National Party MP Vredefort [1915-1921],United Party MP Bloemfontein South [1921-1929], Bloemfontein City [1938-1953]; Senator Natal [1954-1955]; Minister of Justice [1939-1945]. Labour [1945-1948], Social Welfare [1948].
COVERAGE 1901-1959; 69 Files; 1,22 Metres.
Keywords: STEYN, Colin Fraser; Inventories; Politicians; National Party